ANALISIS PELAKSANAAN BAURAN PROMOSI PADA PT JALUR NUGRAHA EKA KURIR (JNE) PEKANBARU - Riyanda "; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The marketing strategy includes products/services, promotion, pricing and place. Promotion as one of the factors that may affect the interests of consumers, consisting of several alternative strategies, namely publicity, advertising, sales promotion and personal selling . PT . JNE has implemented a variety of ways with the publicity and promotion of personal selling to increase sales of services such as employee uniforms in order to make the company better known by the public. Other promotional strategy is to make the sticker affixed to the truck freight cars, put stickers on cargo ships, etc. This study aims to determine the promotional mix strategies of PT Jalurnugraha Eka Courier (JNE) Pekanbaru.The population of this research are the user of PT JNE Pekanbaru as many as 78 120 people . To take the sample is use the Slovin model, samples taken are 100 people with accidental sampling method . The data analysis using descriptive methods .The results showed that the promotion mix in PT JNE can be categorized Less Precise because of the 4 promotional mix that applied in the company, only publicity that has been applied correctly. Personal selling, of the three indicators used , no single indicator is applied properly by the company , so the personal selling in PT JNE Branch categorized Inappropriate. Publicity, of the three indicators used only two indicators were applied properly by the company, so the company implemented publicity Less Precise. Advertising , of the three indicators used , there is only one indicator that is applied with proper promotion through the internet. It concluded that the company implement inappropriate advertising. Sales promotion, of the three indicators used, none of the indicators were applied properly by the company, it means that sales promotion is Not Properly applied by the company.Keywords : Promotion Mix, Personal selling, Publicity, Advertising, Sales Promotion